Association of maternal psychological distress and milk cortisol with infant temperament and growth - Mahsa Feizabad; Fatemeh Pourhabibi-Zarandi; Reza Barati-Boldaji; Maral Hashemzadeh; Mohammad Hadi Eskandari; Masoumeh Akhlaghi (Scientific Reports)
Abstract During psychological distress, breastmilk cortisol levels are increased and may affect infant temperament and behavior. We studied the association of maternal psychological distress and milk cortisol with infant temperament and growth. Using a cross-sectional design, 140 mother–infant dyads were studied. Infants were 3–4 months old and were exclusively breastfed. Maternal psychological distress and infant temperament were assessed by the depression, anxiety, and stress scale and infant behavior questionnaires, respectively. Milk cortisol concentrations and growth indices were determined. Maternal obesity and infant growth indicators did not show significant associations with the severity of maternal distress. Negative emotionality of infants had the most frequent and strongest association with maternal psychological distress: depression (b = 5.38; 95% CI 3.04, 7.72; P < 0.001), anxiety (b = 6.01; 95% CI 3.70, 8.32; P < 0.001), and stress (b = 4.10; 95% CI 2.74, 5.45; P < 0.001). The association existed both directly and indirectly through the mediating effect of breastmilk cortisol. Regulatory capacity was positively associated with maternal depression (b = 3.73; 95% CI 1.10, 6.37; P = 0.006) and anxiety (b = 3.02; 95% CI 0.33, 5.71; P = 0.030), but the association was not mediated by milk cortisol. Surgency was not associated with maternal depression, but it had negative associations with maternal anxiety and stress. Infant temperament was also reciprocally associated with maternal emotional states and breastmilk cortisol concentrations. Overall, this study highlighted associations between maternal psychological distress and infant mood and temperament, emphasizing the mediating effect of breastmilk cortisol.